Legal Analysis of Acceptable Transfer (Cassie) to Third Parties in the Decision Case of North Jakarta State Court Number 471/Pdt.G/2019/PN.Jkt.Utr - Linguis Muhammad Yunus Atahiah; Karli Karli (LEGAL BRIEF, 2022)
Submission of bills on behalf of (cessie) as stipulated in Article 613 of the Civil Code where the submission is carried out to make a deed, where the deed of claims on behalf of said cessie deed. This research aims to find out how the transfer of receivables (cessie) to third parties according to the Civil Code and what are the legal consequences of the Receivable Buyer (cessor) for objects caused by the Transfer of Receivables (cessie) in the North Jakarta District Court Decision Case Number 471/Pdt.G/2019 /PN.Jkt.Utr. This research was designed with a normative juridical approach with a statute approach, case approach and conceptual approach. Sourced data obtained from library research. Data were analyzed by descriptive analysis method. Based on the results of the analysis, it was found that in the Case Decision of the North Jakarta District Court Number 471/Pdt.G/2019/PN.Jkt.Utr that was a delegate (transfer of debtor's obligations), namely the Debtor (Plaintiff) received a Letter from Defendant I with Letter No. 18/COL/10608 and Letter No. 18/COL/10611 Subject: Notification of Transfer of Receivables. Defendant I as a Creditor has the right to make a Transfer of Receivables (Cessie) to another party. Legal Consequences of Transfer of Receivables (cessie) is declared valid because Cessie can be done through an authentic deed or private deed, with the main requirement for the validity of the cessie is notification of the cessie to the debtor for approval and recognition.